A metáfora e sua função persuasiva em artigos de opinião sob a perspectiva da lingüística sistêmico-funcional - Vieira, Wander Marques (2008)
Opinion articles have an important symbolic function of, seemingly, sharing the paper s opinion by covertly bolstering up the assertion that the other sections, conversely, are pure facts or reports . Once signed, they not necessarily represent the paper ideological stance (O Estado de São Paulo); however, Kitis & Miliapes (1996) claim that by being in it, they allow the readership to invest them with the same authority and reliability ascribed to the newspaper. In so being, we can use for the opinion article the very same Fowler s words (1991), when he claims that what distinguishes an editorial is not the expression of values and beliefs, but the textual strategies being used to stand out the speech acts of values and beliefs . This work analyses Gaudêncio Torquato s articles, published on a weekly basis, in O Estado de São Paulo, from the viewpoint of the Critical Linguistics , which proposes that analysis using appropriate linguistic tools, and referring to relevant historical and social contexts, can bring ideology, normally hidden through habitualization of discourse, to surface for inspection , Fowler (1991: 89). While the focus of the traditional analysis discourse is on the meanings established between sentences and utterances, in CDA the focus is on the selections which are made in constructing texts, on factors that constrain and determine these selections, and on their effect. According to Charteris-Black (2004), metaphor is one of these conscious linguistic choices that conceals underlying social processes, and metaphor analysis can aid in the identification of implicit textual content, and metaphor constitutes verbal evidence for an underlying system of ideas or ideology . Kress & Hodge (1993: 15) propose that ideology involves a systematically organized presentation of reality . With this is mind, the authors claim that metaphor is vital in creating such a presentation of reality. Stemming from a corpus of five opinion articles, the aim of this research is, by means of a metaphor-based study, to understand the functioning of this linguistic resource. It is through metaphor that the author expresses his attitudinal position on x the country s political developments, and manages at the same time to directly avoid threatening the face of the people involved, send out his message and persuade his readership. In my analysis, I resort basically to the Systemic-Functional Linguistics (Halliday, 1985; 1994), and its contributors, the Relevance Theory (Sperber & Wilson (1986; 1995), the Goatly s notions (1997) and the developments the theories have been receiving. According to Eggins (1994), what differentiates the SFL is that it seeks to develop a theory of language as a social process and a methodology which allows detailed and systematic description of linguistic patterns. The SFL is considered the more suitable theory-methodological approach to Critical Discourse Analysis (Fowler, 1991); Fairclough, 1992). On the other hand, Charteris-Black (2004) and Fairclough (1999a) analyse metaphor based on Halliday s Functional Linguistics (1985; 1994)